Sex-differences in oral anticoagulation therapy in patients hospitalised with atrial fibrillation: a nationwide cohort study. (3rd October 2022) - Lee, K; Doudesis, D; Bing, R; Astengo, F; Perez, J; Anand, A; McIntyre, S; Bloor, N; Sandler, B; Lister, S; Pollock, K; Qureshi, A; et al.
Abstract: Background: Important disparities in the treatment and outcomes of women and men with atrial fibrillation are well recognized. Whether introduction of direct oral anticoagulants has reduced disparities in treatment is uncertain. Methods: All patients who had an incident hospitalization from 2010 to 2019 with non-valvular atrial fibrillation in Scotland were included in this cohort study. Community drug dispensing data were used to determine prescribed oral anticoagulation therapy and comorbidity status. Logistic regression modelling was used to evaluate patient factors associated with treatment with vitamin K antagonists and direct oral anticoagulants. Results: A total of 172, 989 patients (48% women [82, 833/172, 989]) had an incident hospitalization with non-valvular atrial fibrillation in Scotland between 2010 and 2019. The proportion of patients with thromboembolic risk factors (CHA2DS2VASc score >0 in men and >1 in women) treated with oral anticoagulation therapy increased from 36.8% to 66.3% over this 10-year period. By 2019, factor Xa inhibitors accounted for 83.6% of all oral anticoagulants prescribed, while treatment with vitamin K antagonists and direct thrombin inhibitors declined to 15.9% and 0.6%, respectively. Women were less likely to be prescribed any oral anticoagulation therapy compared to men (adjusted odds ratio, aOR 0.68 [95% CI, CI 0.67–0.70]). This disparity was mainly attributed to vitamin K antagonists (aOR 0.68 [95% CI 0.66–0.70]), whilst there was less disparity in use of factor Xa inhibitors between women and men (aOR 0.92 [95% CI 0.90–0.95]). At 1 year following hospitalization with atrial fibrillation, patients not prescribed oral anticoagulation therapy were more likely to have subsequent major adverse cardiovascular events compared to those prescribed with oral anticoagulation therapy (38.8% [15, 380/39, 608] versus 17.0% [6, 761/39, 671] in women and 35.2% [12, 977/36, 868] versus 16.4% [7, 395/45, 093] in men). Conclusions: Women with non-valvular atrial fibrillation were significantly less likely to be prescribed vitamin K antagonists compared to men. Most patients admitted to hospital in Scotland with incident non-valvular atrial fibrillation are now treated with factor Xa inhibitors and this is associated with less treatment disparities between women and men. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This study was supported by the British Heart Foundation through a Clinical Research Training Fellowship (FS/18/25/33454), Intermediate Clinical Research Fellowship (FS/19/17/34172), Senior Clinical Research Fellowship (FS/16/14/32023) and a Research Excellence Award (RE/18/5/34216), and a research grant to NHS Lothian from Bristol Myers Squibb Pharmaceuticals Ltd and Pfizer UK Ltd.